A Microstructural Model of SMA with Microplastic Deformation and Defects Accumulation: Application to Thermocyclic Loading. (2015) - Belyaev, F.; Evard, M.; Volkov, A.; Volkova, N.
Abstract: The proposed microstructural model of the functional-mechanical behavior of shape memory alloys (SMA) is aimed to describe reversible phase deformation, microplastic deformation due to accommodation of martensite and evolution of deformation defects. The internal variables of the model are volume fractions of the Bain's variants of martensite and measures of microplastic deformation associated with these variants. The proposed microplastic flow rule accounts for kinematic and isotropic hardening. The microplastic flow force and the back force characterizing the two modes of hardening are related to the densities of reversible and irreversible deformation defects. For the variation of the defect densities a special evolution equation is formulated. Model verification is carried out through simulation of the reversible and irreversible strain evolution under thermocycling across the interval of the phase transformations. It is shown that the model can describe a rather big irreversible strain in the first thermocycle and its fast decrease with the number of cycles.